2022
DOI: 10.1088/1361-6560/ac79f9
|View full text |Cite
|
Sign up to set email alerts
|

TOPAS-nBio simulation of temperature-dependent indirect DNA strand break yields

Abstract: Current Monte Carlo simulations of DNA damage have been reported only at ambient temperature. The aim of this work is to use TOPAS-nBio to simulate the yields of DNA single-strand breaks (SSBs) and double-strand breaks (DSBs) produced in plasmids under low-LET irradiation incorporating the effect of the temperature changes in the environment. A new feature was implemented in TOPAS-nBio to incorporate reaction rates used in the simulation of the chemical stage of water radiolysis as a function of temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(74 reference statements)
1
4
0
Order By: Relevance
“…The observations in this work reflect the results from a number of publications regarding the range of electrons in liquid water, as a function of electron energy 11,26–30 . In particular, it is evident that the majority of DNA damage is indirect which is in agreement with the results of Ramos et al., 31 who reported that the chemical processes are responsible for 80%$\approx 80\%$ of the DNA damage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observations in this work reflect the results from a number of publications regarding the range of electrons in liquid water, as a function of electron energy 11,26–30 . In particular, it is evident that the majority of DNA damage is indirect which is in agreement with the results of Ramos et al., 31 who reported that the chemical processes are responsible for 80%$\approx 80\%$ of the DNA damage.…”
Section: Discussionsupporting
confidence: 91%
“…The free radical probability of 0.4, DSB separation of 10 bp, and the ionization and damage energy thresholds (12.6 and 17.5 eV, respectively) adopted in our damage estimation algorithm are all based on values utilized in previously published works 23,36 . While some authors noted a dependence of DNA damage on temperature for TOPAS‐nBio simulations, 31 deviation from the default simulation parameters were beyond the scope of this work but should be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Mendez et al [ 60 ] conducted a simulation study on the temperature dependance of single (SSB) and double (DDB) indirect DNA strand breaks. Their results were compared to experimental data, showing a linear relation between the yield of SSB and DDB with temperature and dose.…”
Section: Discussionmentioning
confidence: 99%
“…TOPAS-nBio allows for simulation of an extended list of chemical species such as O 2 (2.4), -O 2 (1.75), HO 2 (2.3) and -HO 2 (1.4) [40]. These models were successfully applied to predict temperature dependent DNA strand-break yields in plasmid DNA [127]. However, in general it has to be noted, that the simulation of the chemical stage with extended time scales up to the microseconds and short time steps is comparatively slower than the simulation of the scattering processes during the physical stage.…”
Section: )mentioning
confidence: 99%